Perbedaan Pengaruh Pemberian Neuromuscular Electrical Stimulation (Nmes) Sebelum Dan Sesudah Latihan Terhadap Peningkatan Kekuatan Otot Biceps Brachii Pada Atlet Pencak Silat Universitas Muhammadiyah Surakarta - Mahadika, Abel; , Totok Budi Santoso , S.Fis , MPH (2017)
Background: In the pencak silat athlete biceps muscle including the dominant use. In the basic techniques of using the catch leg kickback in advance, requiring a strong biceps muscle strength. The importance of the function of muscle strength in the sport of pencak silat in order to prevent any risk of injury and competencies associated with a pencak silat game, this is what attracted the attention of researchers to conduct this research. Objective: This study aimed to determine the difference in the effect of Neuromuscular Electrical Stimulation / NMES between before and after exercise to increase muscle biceps strength in athletes pencak silat method muscle group. Methods: This study is a quasi-experimental research with experiment quasy approach. The research sample was taken based on the techniques of the total population was held in the Auditorium Muhammad Djazman universities of Tapak Suci UMS Unit 006, using a method NMES muscle group. The treatment group was divided into 2 groups, ie groups before exercise and after exercise groups each group of 5 people. This study design is a pre and post test with Two Group Design with data analysis using non parametric tests. Results: Based on statistical tests using paired sample T-test showed a significant in the muscle groups before and after a workout in of Tapak Suci UMS with a value of p = 0.005 (> 0.05) so there is the effect of NMES on the method of muscle groups before and after exercise , Statistical test for different test the effect of NMES before exercise and after exercise using Mann Whitney Test significance values post p= .032 (p> 0.05)